Refleksi Unit Usaha Simpan Pinjam dan Transformasi Digital Bumdes Karya Sejahtera Desa Geneng, Jepon - Rosalia, Amelia Choya Tia; Joko Priyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Geneng Village, located in Jepon Sub-district, Blora Regency, has a population of 2,544 residents spread across four hamlets. In 2019, the village established the Village-Owned Enterprise (BUMDes)